Stakeholders perspectives on Workbased Learning (WBL) implementation in Malaysia: a review / Wan Nur Najmina Najwa Wan Mokhtar ... [et al.] - Wan Mokhtar, Wan Nur Najmina Najwa; Mohamad, Norhaya Hanum; Wan Nawawi, Wan Nazriah; Anuar, Jazira (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
This review focuses on assessing the engagement of work-based learning (WBL) stakeholders in curriculum implementation in Malaysia. By reviewing the literature, this article seeks to expand existing knowledge on the role of stakeholders in WBL program implementation. It seeks to provide a review that expands the literature on WBL stakeholders and programs. This study was conducted to gain insight into the role of stakeholders in implementing a WBL program, especially in the hospitality sector. By understanding their roles, stakeholders can improve their engagement in WBL program implementation to meet the current need for competent and well-prepared graduates to work in the industry. This review made extensive use of secondary sources of data collected from recent studies conducted by other researchers from journals, articles and websites. Findings indicated that there are four (4) main themes derived from the literatures namely WBL definitions, purposes, significance and stakeholders categories.